Bioevaluation of Ranatuerin-2Pb from the Frog Skin Secretion of Rana pipiens and Its Truncated Analogues - Xiaowei Zhou; Daning Shi; Ruimin Zhong; Zhuming Ye; Chengbang Ma; Mei Zhou; Xinping Xi; Lei Wang; Tianbao Chen; Hang Fai Kwok (Biomolecules, 2019)
Antimicrobial peptides (AMPs) are considered as a promising agent to overcome the drug-resistance of bacteria. Large numbers of AMPs have been identified from the skin secretion of Rana pipiens, including brevinins, ranatuerins, temporins and esculentins. In this study, the cDNA precursor of a broad-spectrum antimicrobial peptide, ranatuerin-2Pb, was cloned and identified. Additionally, two truncated analogues, RPa and RPb, were synthesised to investigate the structure-activity relationship of ranatuerin-2Pb. RPa lost antimicrobial activity against Candida albicans, MRSA, Enterococcus faecalis and Pseudomonas aeruginosa, while RPb retained its broad-spectrum antimicrobial activity. Additionally, ranatuerin-2Pb, RPa and RPb demonstrated inhibition and eradication effects against Staphylococcus aureus biofilm. RPb showed a rapid bacterial killing manner via membrane permeabilization without damaging the cell membrane of erythrocytes. Moreover, RPb decreased the mortality of S. aureus infected Galleria mellonella larvae. Collectively, our results suggested that RPb may pave a novel way for natural antimicrobial drug design.